Assessment of Public Relations Strategies Adopted for Sensitization by the Presidential Steering Committee on COVID-19 in Abuja and Lagos - Daramola Folashade Patience; Musa Mathias; Josiah Sabo Kente (International Journal of Education, Culture, and Society, 2026)
Effective public communication is essential during public health emergencies because it shapes awareness, promotes preventive behavior, and strengthens public confidence in crisis-management institutions. This study assesses the public relations strategies adopted by the Presidential Steering Committee on COVID-19 to sensitize the public in Abuja and Lagos. Guided by agenda-setting theory, the study employed a survey research design and used a questionnaire to collect data from all 107 members of the Presidential Steering Committee through census sampling. The findings indicate that the Committee effectively disseminated information on COVID-19 preventive measures through multiple conventional and digital media channels, and respondents generally perceived its communication efforts favorably. The strategies employed included active engagement with traditional and online media, transparent communication, and proactive measures to counter misinformation. Although respondents’ assessments of the effectiveness of these strategies varied, the findings demonstrate that the Committee’s public relations activities played an important role in disseminating essential information, mitigating the effects of the pandemic, and fostering public confidence in Abuja and Lagos. The study concludes that diversified, transparent, and responsive public relations strategies are essential for effective crisis communication. It therefore recommends the sustained implementation of robust public relations practices to strengthen public sensitization, address misinformation, and improve institutional communication during public health emergencies.